Hedgehog signaling stimulates Tenascin C to promote invasion of pancreatic ductal adenocarcinoma cells through Annexin A2. Issue 5 (3rd September 2017) - Foley, Kelly; Muth, Stephen; Jaffee, Elizabeth; Zheng, Lei
ABSTRACT: Pancreatic adenocarcinoma (PDA) is characterized by a dense desmoplastic reaction that comprises 60–90% of the tumor, while only 10–40% of the tumor is composed of malignant epithelial cells. This desmoplastic reaction is composed of stromal fibroblast cells, extracellular matrix proteins, and immune cells. Accumulating evidence has suggested that the stromal and epithelial cell compartments interact during the pathogenesis of this disease. Therefore, it is important to identify the signaling pathways responsible for this interaction to better understand the mechanisms by which PDA invades and metastasizes. Here, we show that secreted stromal factors induce invasion of PDA cells. Specifically, hedgehog signaling from the tumor cells induces tenascin C (TnC) secretion from the stromal cells that acts back upon the tumor cells in a paracrine fashion to induce the invasion of PDA cells through its' receptor annexin A2 (AnxA2). Therefore, blocking the interaction between TnC and AnxA2 has the potential to prevent liver metastasis in PDA.